Analisis Penerapan Intervensi Mobilisasi Dini untuk Mempercepat Penyembuhan Luka Post SC pada Ibu Post partum: Systimatic Review - Niah Kurniasih; Esther Lenny D Marisi; Dea Aprilya (Jurnal Ventilator, 2026)
Background Sectio caesarea is an action to give birth to a fetus by making an incision in the uterus through the abdominal wall. The action of sectio caesarea can also have an impact on fulfilling the patient's basic needs and can also cause pain in the surgical scar, for example, damage to skin/tissue integrity, disturbances elimination of urine, impaired nutrition and fluid intake, impaired activity. The presence of scars after a caesarean section operation will cause pain in the patient. One of the basic concepts of care in the postpartum period for post-cesarean section patients is that early mobilization is given after a caesarean section. Objective: To know the management of early mobilization in accelerating wound healing in post-caesarean section patients. With Network Integrity Disruption. Method: This method uses a non-systematic literature review study based on relevant references from related titles. The data source is based on the most updated journal from 2019-2024. Results: Based on 5 journals that have been reviewed, the results obtained after implementing early mobilization show that there is an influence of early mobilization in wound healing in post-Op Sectio Caesarea patients.